Desenvolvimento de vestuário em jeans para mulheres, incluindo as pós-bariátricas - Francisco, Carolina (2016)
It shows a great difficulty for people who like to consume denim clothes to find pieces that satisfy them for comfort. The same applies to the post-bariatric that after surgery, undergo rapid loss of many kilos, causing skin leftovers and apparent laxity. With these post-surgical results, often the functions that this new body needs are not met by the market. The work is based on research on ergonomic functions related to fashion, highlighting the comfort within them, in order to meet the different needs of both those who consume the jeans for like as for post-bariatric. It is also researching bariatric surgery, why people resort to it and cites different surgical procedures. It is studying the appropriate material to the public, noting that it is more consistent use of structured fabrics that hide the flab and give security to the consumer. However, it also adds up the pursuit of jeans use in the manufacture of parts of post-bariatric. It is also considering anthropometric questions, in order to verify the differences in body measurements of people who have undergone bariatric surgery and others who did the procedure. Used bibliographic research methods and data collection through the application of a questionnaire to each audience mentioned. The research results in a gap in the fashion market, meeting the needs of specific audiences, which has been expanding in society and increasing consumption.